Pengaruh pembelajaran fikih berbasis Deep Learning terhadap motivasi siswa dalam bersedekah di MTs Negeri 2 Pacitan - Nur Azizah, Lusiva; Hidayati, Fithri; Abdan, M. Rohmad (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2026)
This research is motivated by the low initiative of students to give alms (infak) and their heavy reliance on teacher instructions, a result of Fiqh (Islamic Jurisprudence) learning that remains predominantly theoretical and conventional. Consequently, the value of generosity has not been fully internalized as an intrinsic awareness. This study aims to analyze the implementation of the Deep Learning method in transforming students' motivation for almsgiving (sedekah), ensuring it transcends rote routine to become an independent and sustainable social character. This study employs a quantitative research method with an ex-post facto design. Data were collected by distributing questionnaires which had been tested for validity and reliability—to respondents via WhatsApp groups using Google Forms, supplemented by observations. Data analysis was conducted using IBM SPSS 27, encompassing classical assumption tests and hypothesis testing. The results of the classical assumption tests met all criteria for normality, linearity, and homoscedasticity. Statistical analysis through simple linear regression yielded the regression equation Y = 8.100 + 0.866X with a significance value of 0.000 < 0.05, a calculated t-value of 9.842 > 1.989 (t-table), and a coefficient of determination (R2) of 51.3%. These findings demonstrate that Deep Learning-based Fiqh instruction has a significant and positive influence on students' motivation for almsgiving at MTs Negeri 2 Pacitan. Overall, this research confirms that the null hypothesis is rejected and the alternative hypothesis is accepted. Abstrak Penelitian ini dilatarbelakangi oleh rendahnya inisiatif berinfak dan ketergantungan siswa pada instruksi guru akibat pembelajaran Fikih yang masih bersifat teoretis-konvensional, sehingga nilai kedermawanan belum terinternalisasi menjadi kesadaran intrinsik. Penelitian ini bertujuan untuk menganalisis penerapan metode Deep Learning dalam mentransformasi motivasi bersedekah siswa agar tidak sekadar menjadi rutinitas hafalan, melainkan menjadi karakter sosial yang mandiri dan berkelanjutan. Penelitian ini menggunakan metode penelitian kuantitatif dengan jenis penelitian ex-post facto. Data dikumpulkan dengan mendistribusikan kuesioner yang telah diuji validitas dan reliabilitasnya kepada responden melalui WhatsApp Group dalam bentuk Google Form serta observasi. Teknik analisis data menggunakan bantuan Tools Manager IBM SPSS 27 meliputi uji asumsi klasik dan uji hipotesis. Hasil uji asumsi klasik memenuhi semua kriteria normalitas, linieritas, dan tidak terjadi gejela heteroskedastisitas. Secara analisis statis, uji regresi linier sederhana menghasilkan persamaan regresi Y=8.100+0.866x dengan nilai signifikansi sebesar 0,000<0,05, nilai t-hitung sebesar 9.842>t-tabel(1,989), dan nilai koefisien determinasi sebesar 51.3%. Temuan ini membuktikan bahwa Pembelajaran fikih berbasis Deep Learning berpengaruh signifikan dan positif terhadap motivasi siswa dalam bersedekah di MTs Negeri 2 Pacitan. Secara keseluruhan, penelitian ini telah membuktikan hipotesis nol ditolak dan hipotesis alternatif diterima.